Pre-registration: Examining the Impact of Light Exposure on Emotions, Psychic Health and Behaviours - Berglund, Danielle; Hadlaczky, Gergö; Alvarsson-Hjort, Jesper (Karolinska Institutet, 2026)
This dataset is connected to a study investigating how blue light exposure affects emotions, psychic health, and behaviours. The data material in this publication is a simulation of a forthcoming dataset.

The forthcoming dataset will consist of three different data sources: self-reports and aggregated behavioral data from a survey, electrocardiograms, and behavioral data from an N-back task. A detailed description of the data collection and dataset can be found in the attached file "Data_collection_protocol.pdf". The codebook for the self-report measures consists of 286 rows, of which 14 are question texts and therefore not variables. The total number of variables is thus 272, which is the same as in the simulated dataset.

Detta dataset är kopplat till en studie som undersöker hur exponering för blått ljus påverkar känslor, psykisk hälsa och beteenden. Datamaterialet i denna publicering är en simulering av kommande dataset.

Det kommande datamaterialet kommer bestå av tre olika datamängder: självskattningar och aggregerade beteendedata från en enkät, elektrokardiogram samt beteendedata från en N-backuppgift. En utförlig beskrivning av datainsamlingen och datamaterialet finns i den bifogade filen "Data_collection_protocol.pdf". Kodboken för självskattningar består av 286 rader, varav 14 är frågetexter och inte variabler. Antalet variabler uppgår därmed till 272, samma antal som i det simulerade datamaterialet.
Pre-registrering: Undersökning av påverkan av ljusexponering på känslor, psykisk hälsa och beteenden
Keywords: HUMAN BEHAVIOUR; MÄNSKLIGT BETEENDE; Emotions; Emotioner; PERCEPTION; VARSEBLIVNING; Lighting; Belysning; Psychophysiology; Psykofysiologi; PSYCHOLOGICAL WELL-BEING; PSYKISKT VÄLBEFINNANDE; PSYCHOLOGY; PSYKOLOGI; Psychology (Excluding Applied Psychology); Psykologi (exklusive tillämpad psykologi); Public health; Folkhälsa; Public Health, Global Health and Social Medicine; Folkhälsovetenskap, global hälsa och socialmedicin